THE BEST PRACTICE SISTEM PENJAMIN MUTU INTERNAL (SPMI) KEPALA SEKOLAH SMA NEGERI 7 DENPASAR - Widiawati, Cokorde Istri Mirah Kusuma (LPPM IKIP PGRI Bali, 2019)
Educational quality assurance aims to meet or exceed National Education Standards (SNP). The approach used to improve the quality of learning and / or the quality of education is the scientific approach. The aim of the quality assurance is to maintain and improve the quality of school education in a sustainable manner, which is carried out internally to realize the vision and mission of the school, and to fulfill the needs of stakeholders through the implementation of learning in schools. The vision of Denpasar 7 Public High School is to excel academically, non-academically, with character, care for the environment, master information technology. The motto of the school of Matuha, Migasa, Mawredya means getting older, more powerful, growing. The expected results of the implementation program of model school development are that schools can implement education quality assurance independently, can improve quality according to National Education Standards, have a quality culture, and train teacher professionals in carrying out their duties.         High School 7 located on Cambodia Street No. 9 Denpasar Bali, with Principal Dra. Cokorde Istri Mirah Kusuma Widiawati (2016 until now). Both in terms of building arrangement, facilities, human resources, the system implemented, student achievement, graduates' results, etc. make this school able to compete in the city of Denpasar. The teaching staff owned by the school are 77 people, consisting of: provincial civil servants 38 people, PNS DPK 2 people, and non-PNS 36 people and total employees 41 people consisting of 7 civil servants, honorarium 34 people. The number of students is 1,328 people with a total number of 36 students. Class X is 419 people, class XI is 432 people, and class XII is 477 people. The awards obtained by the school in the past few years were 31, while the awards obtained by students were 19 academic and non-academic achievements both at provincial, national and overseas levels. In this case in the 7th Denpasar Senior High School has an extracurricular 52 branches. On the national exam in 2018, the national exam scores of the Denpasar Public High School 7 experienced a very significant increase. For the specialization of MIPA, the 7th Public High School in Denpasar was ranked 6th in Bali and Social Sciences specialization was ranked second for the average UN in Bali in 2018. SMA 7 Denpasar implemented an 8-hour learning system known as Fullday School. Character education is a priority in education at Denpasar 7 Public High School as part of a mental revolution. The liasi activity will bring a positive impact on the achievement of the pretensions at the 7th Public High School in Denpasar, both academic and non-academic.